THE IMAGES OF MODERN WOMEN PORTRAYED IN TIM STORY’S TAXI MOVIE - DWINISA, AJENG (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Traditional Women, Modern Women, Feminism, Images of Women. This study talks about women and their image that has changed in society. The changes include the traditional image of women into their image in modern society. Images and roles of women often appear in literary works, including films.  One of the films about women is Taxi. Taxi is an action movie which puts women as the most dominant characters. They are Belle Williams, Vanessa, and Lieutenant Marta. The problem of this study is how the images of modern women are portrayed in the movie Taxi. Meanwhile the purpose of this study is to disclose the images of modern women portrayed in Taxi movie. This study is carried out using qualitative approach since the images of modern women of the three female characters in Taxi movie is analyzed in descriptive ways.  Traditionally it is clear enough that women’s place is in the home. However, along with the evolution women’s place is no longer always in home and doing all the housework things. Women in this era also become autonomous decision makers. They now can decide the good or bad for themselves even for the other. Through the female characters in Taxi movie too, women are also represented as independent and do not need men’s protection. Men’s view of women primarily as sexual objects does not change, but now they are also interested in women as people. Women also can use men’s interest to get what they want. Through Belle, Liuetenant Robbins and Vanessa, the new images of women are clearly represented.  The main female characters in Taxi movie, the characteristics of Belle, Lieutenant Robbins, and Vanessa have the similarity, they are beautiful, smart, optimistic, profesional, considerable, good taste, and talented.  Modern women show different images from the traditional expectation on women. The writer suggests for the readers who want to analyze the characters in Taxi movie, the reader may analyze another characters. The next researcher can use a theory of gender reversal which puts Washburn and Jesse as the main figures to be analyzed.